Ghostman [large type] - Hobbs, Roger (Thorndike Press, 2013)
A casino robbery gone wrong compels its orchestrator to call in a favor from a master criminal known only as "Jack," whose activities are subject to mystery and speculation and who must test the limits of his considerable skills in order to protect his anonymity from a closely pursuing FBI.